To the question of current species composition of blackflies (Diptera, Simuliidae) of the Irtysh river in Pavlodar region - Orazbekova, A.; Akhmetov, K.; Burkitbayeva, U.; Aubakir, A. (Fundamental and Experimental Biology, 2025)
The article shows the list of species diversity of the family Simuliidae, noted in Pavlodar Priirtyshye in the period from 2022 - 2024. In the basin of the middle reaches of the Irtysh River (from the border of the Maysky district to the Zhelezinsky district, the border with Russia), the presence of 5 species of blackflies was noted. The identified blackflies belong to the Palaearctic and Holactic species of plastic blackflies capable of living in polluted water bodies: Wilhelmia equine (Linnaeus, 1758), Boophthora erythrocephala (De Geer, 1776), Odagmia ornata (Meigen, 1818), Argentisimulium noelleri (Friederichs, 1920), Simulium reptans (Linnaaeus, 1758). The history of the study of blackflies in Kazakhstan and in the studied area is noted. The frequency of occurrence is indicated, and the bionomics of species for the Pavlodar region is described. Dominant species are identified.